2004
DOI: 10.1016/s0886-3350(03)00672-2
|View full text |Cite
|
Sign up to set email alerts
|

Opacification of a silicone intraocular lens caused by calcium deposits on the optic

Abstract: We describe opacification of a plate-haptic silicone intraocular lens (IOL) caused by calcification in a diabetic patient with asteroid hyalosis. The IOL was explanted 48 months after uneventful phacoemulsification because opacification of the posterior surface was causing significant visual disturbance. Light and scanning electron microscopy and x-ray spectrometry of the explanted IOL showed the opacification consisted mainly of calcium and phosphate, presumably hydroxyapatite, in the form of precipitations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 11 publications
2
35
0
Order By: Relevance
“…14,15 Finally, the occurrence of dystrophic calcification of silicone lenses has been described in eyes with asteroid hyalosis. [16][17][18] More recently, Tanaka et al 19 observed a phenomenon similar to the 6 cases described here in an 83-year-old Japanese patient who had implants with the same IOL design (SI40 NB). The IOL presented with a ''brown haze'' on the first postoperative day.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…14,15 Finally, the occurrence of dystrophic calcification of silicone lenses has been described in eyes with asteroid hyalosis. [16][17][18] More recently, Tanaka et al 19 observed a phenomenon similar to the 6 cases described here in an 83-year-old Japanese patient who had implants with the same IOL design (SI40 NB). The IOL presented with a ''brown haze'' on the first postoperative day.…”
Section: Discussionsupporting
confidence: 79%
“…However, the latter has been observed only in eyes with associated asteroid hyalosis. [16][17][18] Tanaka et al 19 recently reported a case of optic haze of a 3-piece silicone lens, observed on the first postoperative day. One author of the current study had 4 similar cases with the same lens design and reported the clinical aspects.…”
mentioning
confidence: 99%
“…[32][33][34] Four cases were initially reported in the literature, all with silicone plate IOLs in patients with unilateral asteroid hyalosis. 32,33 White deposits appeared late postoperatively on the posterior optic surface only. Two of the 4 reported patients had diabetes.…”
Section: Late Postoperative Iol Opacification/discoloration Silicone mentioning
confidence: 99%
“…Chemical composition of the Allergan silicone IOLs and the sterilization method used were the causes of the haze formation [28, 29]. Wackernagel et al [30] described opacification of a plate-haptic silicone IOL (Chiron Vision C10UB plate-haptic silicone lens) caused by calcification in a diabetic patient with asteroid hyalosis after Nd:YAG laser capsulotomy. Analysis of the lens surface showed calcium, phosphate, and oxygen on corresponding locations within a larger agglomeration of deposits.…”
Section: Discussionmentioning
confidence: 99%